Mosaic embryo transfer-first report of a live born with nonmosaic partial aneuploidy and uniparental disomy 15 - Kamilla Schlade-Bartusiak, Ph.D; Emma Strong, Ph.D; Olive Zhu, M.Sc; Jessica Mackie, M.Sc; Diane Salema, M.Sc; Michael Volodarsky, Ph.D; Jeffrey Roberts, M.D; Michelle Steinraths, M.D (Elsevier, 2022)
Objective: To inform clinicians of the first known case of a live born diagnosed with syndromic partial trisomy 15 and maternal uniparental disomy 15 resulting from a mosaic embryo transfer (MET). We believe that this case will highlight the need for standardized practice guidelines to address the potential risk of MET and the importance of prenatal follow-up after a pregnancy is achieved from a MET. Design: Case report. Setting: In vitro fertilization with preimplantation genetic testing for aneuploidy (PGT-A) and MET was completed at a fertility clinic in Canada. Postnatal testing and diagnosis were performed at the Medical Genetics Department of a hospital in Canada. Patient(s): A newborn male with a diagnosis of partial trisomy 15 and uniparental disomy (UPD) 15. Intervention(s): Mosaic embryo transfer after PGT-A was performed. Diagnostic testing performed after birth included a karyotype, fluorescence in situ hybridization analysis, chromosomal microarray, and microsatellite UPD testing. Main Outcome Measure(s): Confirmed nonmosaic partial aneuploidy of trisomy 15 and UPD15 in a symptomatic newborn conceived from MET. Result(s): Singleton pregnancy was achieved after a double embryo transfer involving 1 embryo diagnosed by PGT-A with high-level mosaic trisomy 15 and high-level mosaic deletion on chromosome 20 (mos(del(20)(q11.23-qter)). Routine prenatal screening and detailed fetal ultrasound did not identify any concerns. Postnatal genetic investigations, triggered by feeding difficulties in the newborn period, diagnosed the proband with maternal UPD15 and a supernumerary marker chromosome composed of 2 noncontiguous regions of chromosome 15. This karyotype is likely resulting from incomplete trisomy rescue occurring on the paternal chromosome 15. Conclusion(s): This case highlights the need for better guidelines and management of pregnancies achieved after MET.